Study of green reductant effects of highly reduced graphene oxide production and their characteristics - Chasanah, Uswatul; Trisunaryanti, Wega; Triyono; Oktaviano, Haryo Satriya; Santoso, Iman; Fatmawati, Dyah Ayu (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
The study of the green reductant effects to produce reduced graphene oxide (rGO) has been completed successfully. The reduction of graphene oxide (GO) was carried out chemically using various reductants such as ascorbic acid (rGO-AA), gallic acid (rGO-AG), and trisodium citrate (rGO-NS). The GO was prepared using the Tour method at a temperature of 65 ? for 6 hours with potassium permanganate: graphite weight ratio 1:3.5. The results showed that rGO-AA had the highest electrical conductivity value of 755.70 S/m, with characteristics such as a surface area of 255.93 m2/g, a pore volume of 0.61 cm3/g, an average pore diameter of 7.10 nm, ID/IG ratio of 1.93, and three graphene layers in the material nanostructure stack. Therefore, it can be concluded that the reduction of GO with ascorbic acid (rGO-AA) is the most effective in producing rGO.